Another New Alkaloid from Corydalis impatiens - Chang Li, Ji; Hua Lin, Yue; Hou, Yong; Li, Ping; Tao Xu, Chun; Peng Li, Gan (Asian Journal of Chemistry, 2012)
A new alkaloid, named impatien B (1) was isolated from the roots of Corydalis impatiens (Pall.) Fisch. The structure of the new compounds was established on the basis of spectroscopic data analysis, especially of their 2D NMR spectra.